The Pragmatics of Politeness in Cross-Cultural Communication - Nkirote, Angela (European Journal of Linguistics, 2024)
Purpose: The general objective of this study was to explore the pragmatics of politeness in cross-cultural communities. Methodology: The study adopted a desktop research methodology. Desk research refers to secondary data or that which can be collected without fieldwork. Desk research is basically involved in collecting data from existing resources hence it is often considered a low cost technique as compared to field research, as the main cost is involved in executive’s time, telephone charges and directories. Thus, the study relied on already published studies, reports and statistics. This secondary data was easily accessed through the online journals and library. Findings: The findings reveal that there exists a contextual and methodological gap relating to the pragmatics of politeness in cross-cultural communities. Preliminary empirical review revealed significant differences in politeness strategies across cultures, highlighting the impact of cultural norms, values, and social structures on communication. High-context cultures, such as many Asian and African countries, conveyed politeness through indirect communication and non-verbal cues, while low-context cultures, like the United States and Western Europe, emphasized directness and clarity. The role of power distance was also crucial, with high power distance cultures showing deference to authority through formal language, unlike low power distance cultures that favored egalitarianism and informality. These findings underscored the importance of cultural sensitivity and awareness in international business, education, and diplomacy, advocating for adaptive communication skills to bridge cultural gaps and enhance mutual understanding. Unique Contribution to Theory, Practice and Policy: The Politeness Theory, Speech Act Theory and Face Negotiation Theory may be used to anchor future studies on the pragmatics of politeness in cross cultural communication. The study recommended expanding theoretical models to include diverse cultural contexts, enhancing intercultural communication training programs, and incorporating these principles into national education curricula. It emphasized the need for organizations to develop clear communication guidelines respecting cultural differences and for diplomatic training to prioritize cultural sensitivity. The study also called for continuous empirical research to keep theoretical models and practical applications relevant, ensuring that both academic and practical approaches to intercultural communication remain effective and responsive to the evolving global landscape.